Metabolic Profiling and Transcriptome Analysis Reveal the Key Role of Flavonoids in Internode Coloration of Phyllostachys violascens cv. Viridisulcata - Wei, Han-tian; Hou, Dan; Ashraf, Muhammad Furqan; Lu, Hai-Wen; Zhuo, Juan; Pei, Jia-long; Qian, Qi-xia (Frontiers in Plant Science, 2022)
Bamboo, being an ornamental plant, has myriad aesthetic and economic significances. Particularly, Phyllostachys violascens cv. Viridisulcata contains an internode color phenotype in variation in green and yellow color between the sulcus and culm, respectively. This color variation is unique, but the underlying regulatory mechanism is still unknown. In this study, we used metabolomics and transcriptomics strategies to reveal underlying mechanism of variation in internode color. A total of 81 metabolites were identified, among those, prunin as a flavanone and rhoifolin as a flavone were discovered at high level in culm. We also found 424 differentially expressed genes and investigated three genes (PvGL, PvUF7GT, and PvC12RT1) that might be involved in prunin or rhoifolin biosynthesis. Their validation by qRT-PCR confirmed high transcript levels in culm. The results revealed that PvGL, PvUF7GT, with PvC12RT1 might promote the accumulation of prunin and rhoifolin which were responsible for the variation in internode color of P. violascens. Our study also provides a glimpse into the phenotypic coloration and is also a valuable resource for future studies.